MASA DEPAN MADRASAH TSANAWIYAH - A Rofik Husen (Jurnal Administrasi Pendidikan, 2021)
The purpose of this study was to determine the background of the establishment of Madrasah Tsanawiyah (MTs) and to see the future after the complexity of the problems faced and the expectations of society when sending their children to school. The method used in this research was qualitative with data collection techniques using a questionnaire. The results showed that most of the goals of the establishment of MTs were originally intended to establish Pesantren. But because the current regulations did not give formal education institution status to Pesantren, the institutions that had been established were transformed into Madrasahs without losing the characteristics of Pesantren Education. Including by continuing to organize classical Islamic books study activities as usual learning activities in Pesantren. The conclusion of this study is that madrasah have the potential to develop and contribute to the world of educa tion in Indonesia, provided that madrasas do not only become subordinated to schools as has been the case so far. Madrasah were established as a middle way for the dichotomy of secularbased national educational institutions with Pesantren. Madrasah Tsanawiyah in par- ticular must have an independent concept and system in order to be able to stand upright with Junior High Schools (SMP) which have a real role in society.